An experimental analysis of fatigue behavior of a welded impeller made by FV520B stainless steel in an over-speed preloading process. (January 2016) - Zhang, Yubo; Xu, Binshi; Wang, Haidou; He, Pengfei; Xing, Zhiguo; Fan, Bonan
Abstract: The purpose of this paper is to evaluate whether over-speed centrifugal force can cause fatigue damage to the welded impeller. Two non-destructive testing techniques of Acoustic Emission (AE) and Infrared Thermography (IRT) were combined to predict the fatigue limit of FV520B and its welded joint. The results indicated that the maximum stress of plastic creep shakedown stage judged by a time–displacement curve was close to the high-cycle fatigue (HCF) limit predicted by the IRT method. The AE technology might have ability to predict the ultra-high cycle fatigue (UHCF) limit. Furthermore, under the present over-speed preloading process, this impeller is located at the pure elastic stage without any fatigue damages. Highlights: The IRT method was proved to be also feasible to predict the HCF limit under a nonzero mean stress. According to the time–displacement curve, the HCF limit could be anticipated, which is similar to that of IRT method. The AE parameters may have the ability to predict the UHCF limit of FV520B and its welded samples. A new analysis method of fatigue behavior of welded impeller in over-speed preloading process was discussed.